South Africa: 5th World Media Summit for Young People in 2007. (Journal of Parents and Teachers, 2014)
This article presents the different world summits that have happened in the past: they explain their achievements and all the trajectory that we still have to go.
Keywords: World Summit; achievements; way to go; youth; childhood.